NON-NATIVE ENGLISH TEACHERS' PERCEPTIONS ABOUT USING TURKISH (L1) IN EFL CLASSROOMS: A CASE STUDY - Sibel Ersel kaymakamoğlu (Informascope, 2019)
This study investigated 5 non-native English teachers' perceptions on Turkish (L1) use in English language (L2) classrooms in the English Preparatory School context of European University of Lefke in the Turkish Republic of Northern Cyprus (TRNC).  The participants were interviewed by using a semi-structured interview and observed by administering a predetermined observation checklist.  Gathered data were analyzed to explore the participants' beliefs and classroom practices regarding the necessity of using L1. The participant non-native English teachers' views   regarding the reasons of using Turkish (L1) were also explored. The results of the  study revealed that the teachers had neutral perceptions about benefiting from Turkish (L1) in their foreign language classes and underscored a place for Turkish (L1) in English (L2) classrooms.  In other words, the majority of the participants did not reject Turkish use; however, due to some restrictions such as English medium education system in the teachers' workplace, nationality factors, and teachers' own teaching philosophy brought some different dimensions to this process.  Overall, the majority of the teachers supported the use of Turkish whereas only one teacher had the opposite view emphasizing that students can become dependent on L1 help which has a high possibility of inhibiting learners from target language acquisition. Keywords: Teachers' perceptions, L1 use, L2 maximization